Nutritional Status Relationship With The Level of Development of Age Toddler (12-36 Months) of Sanur Village in Working Area of Health Center II South Denpasar - Ni Nyoman Pradnya Paramitha Dewi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Picture of the fulfillment of human nutrition can be seen from the nutritional status. Nutritional problems are a frequent health problems facing by society. Toddler age children belonging to the vulnerable groups of nutrients. Toddler age children developmental level is optimal depends on the nutritional quality and quantity of a good and balanced. Nutrition in ages toddler children can not always be implemented perfectly. Lack of nutrition at a young age will affect the development of brain cells, resulting in a children ability to absorb the information to the learning process would be less than optimal so that it will disrupt the development of intelligence. This study aims to determine the relationship between nutritional status with the progression of age Toddler (12-36 months) of ??Sanur Village in working area of Health Center II South Denpasar. This type of descriptive correlation study using cross-sectional design. The sampling technique is simple random sampling with a sample of 111 respondents. Test statistic using the Spearman Rank test. Results showed most respondents have a good nutritional status of the 91 people (82,0%), malnutrition as many as 11 people (9,9%), nutrient over as many as 8 people (7,2%) and poor nutrition as much as 1 person (0,9%). Respondents also have the most appropriate level of development of as many as 89 people (80,2%), doubtful as many as 14 people (12,6%) and the deviation of 8 people (7,2%). Based on the obtained Spearman Rank test p value 0,000 <0,05 then Ho is rejected it means there is a relationship between nutritional status with the progression of age Toddler (12-36 months) of Sanur Village in the working area of ??Health Center II South Denpasar. Based on the results of these studies is recommended for healthcare workers to be more active in providing health education, especially about the Toddler ages development and facilitate in providing referrals to children with nutritional status and level of development is problematic to the hospital with a referral facility for the development of the child.